Whole Blood Polymerase Chain Reaction in a Neonate with Disseminated Herpes Simplex Virus Infection and Liver Failure - Jennifer A. Scoble; Mark A. Underwood (Thieme Medical Publishers, Inc., 2013)
Abstract A late preterm neonate born by cesarean section with intact membranes presented at 9 days of life with shock and liver failure. Surface cultures were negative but whole blood polymerase chain reaction was positive for herpes simplex virus type 2, underscoring the value of this test in early diagnosis of perinatally acquired disseminated herpes simplex virus infection without skin lesions.